Importance of biofilm in Candida parapsilosis and evaluation of its susceptibility to antifungal agents by colorimetric method - Růzicka, F; Holá, V; Votava, M; Tejkalová, R (Folia microbiologica, 2007)
The ability of C. parapsilosis (an important cause of nosocomial infections) to produce biofilm was evaluated in 32 bloodstream isolates and 85 strains isolated from skin. The biofilm formation was found in 19 (59%) blood isolates and only in 33 (39%) isolates from skin. The antifungal susceptibility was assessed for amphotericin B, itraconazole and voriconazole in planktonic and biofilm form of the 19 biofilm-positive bloodstream strains by broth microdilution method according to NCCLS standards. The method was modified by the use of resazurin as a colorimetric indicator of the metabolically active cells which makes the determination of the effect of antifungal agents easier. Biofilm forms of all strains were more resistant than their planktonic form.
Keywords: Antifungal Agents; Drug Resistance, Fungal; fungemie; Candida; infekce spojené se zdravotní péčí; Microbial Sensitivity Tests; antifungální látky; fungální léková rezistence; lidé; Cross Infection; Biofilms; Humans; mikrobiální testy citlivosti; mikrobiologické techniky; kolorimetrie; Fungemia; biofilmy; Microbiological Techniques; Colorimetry